Psychological Services in Russian Universities: What Do We Have and Where We Are Going? - E. V. Gorbunova; I. E. Krylova (Высшее образование в России)
Psychological well-being of students is becoming one of the priorities of higher education today. This paper is devoted to the study of the work experience of psychological services in Russian universities. The results are based on the data of semi-structured interviews with 15 heads of psychological services of Russian universities. The interview data show that the main directions of the services’ work are following: counseling, preventive-educational measures, diagnostic, adaptation, and nurturing. In turn, during the pandemic the services adapted their activities by transitioning to the online format and creating of hotlines for emergency psychological help. At the same time, psychological services face such problems as lack of funding, difficulties in building interaction with psychiatric organizations, conflict of interests between university management and the service management in their activities. Nevertheless, the main trend for the psychological services development is to build a system of psychological support involving different levels of university hierarchy. The results of the study can be used to design a model of university psychological services, as well as to make practical decisions about the development of the psychological services network in Russian universities.